The Sexual Violence Legislation Act 2021: Pre-Recorded Cross-Examination and the Right to a Fair Trial - Hollywood, Cait Verity (Victoria University of Wellington Law Review, 2022)
This article analyses the provisions of the Sexual Violence Legislation Act 2021 that offer witnesses in sexual cases access to pre-recorded cross-examination as an alternative method of giving evidence. The Act is intended to reduce the trauma of sexual violence victims in court whilst preserving the fairness of the trial. The Act prima facie entitles witnesses to access alternative evidence methods, but judges retain a discretion under s 106G to prevent the use of pre-recorded cross-examination. Under s 106G, the judge must do so where the pre-recorded cross-examination presents a real risk to the fairness of the trial. This article evaluates how judges are likely to exercise their discretion under s 106G. I recount the contemporary notion of a fair trial through the lens of the New Zealand Bill of Rights Act 1990 and identify areas of tension between defendants’ fair trial rights and witnesses’ interests. I assess how the realities of the system render pre-recorded cross-examination workable only at the expense of defendants’ fair trial rights. Consequently, judges will almost always be compelled to make orders under s 106G preventing pre-recorded cross-examination. The Act is unfit for its purpose of expanding the availability of alternative evidence for witnesses and improving the justice process for sexual violence complainants.